Physico-chemical properties, spreadability and consumer acceptance of low-sodium cream cheese - Lučan Čolić, Mirela; Ranilović, Jasmina; Slačanac, Vedran; Cvetković, Tanja; Primorac, Ljiljana, inženjerka prehrambene tehnologije; Gajari, Davorka; Tomić-Obrdalj, Helena; Jukić, Marko, biotehnolog; Lukinac Čačić, Jasmina (2020)
The present study was performed to investigate the possibility of sodium reduction in cream cheese by partial reduction and substitution of sodium by potassium based salt. Four salt treatment were selected by preliminary study: 100 % NaCl (control), NaCl reduced to 65 % (T1), 35 % of NaCl substituted by KCl (T2), and KCl-based salt mixture Salut® which contains offflavours masking compound (T3). The study was evaluated physico-chemical attributes, colour, spreadability, sensory acceptance, as well as level of intensity of specific attributes of low-sodium cream cheese. Sodium reduction not influenced on the protein, fat and moisture content, water activity, acidity and the colour of cream cheese (P>0.05). However, sodium reduction significantly influenced to mineral composition, spreadability and sensory properties. The use of potassium salt substitutes significantly increased the value of K:Na ratio. Cheese containing commercial salt replacer Salut® had the closest hedonic score to control cheese compared to other replacers. The current research demonstrates that sodium content can be reduced by 35 % in cream cheese using a nutritionally valuable potassium-based salt mixture, without compromising the consumer acceptance.
Istraživanje je provedeno kako bi se istražila mogućnost smanjenja natrija u krem siru, djelomičnom redukcijom odnosno zamjenom natrija pomoću kalijevih soli. Preliminarnim ispitivanjem odabrana su 4 načina soljenja: 100 % NaCl (kontrola), NaCl snižen na 65 % (T1), 35 % NaCl-a zamijenjeno KCl-om (T2), i mješavina soli Salut® na bazi KCl-a koja sadrži i tvari za prikrivanje stranih okusa (T3). Istraživanjem su ispitivana fizikalno-kemijska svojstva, boja, mazivost, prihvatljivost, kao i stupanj intenziteta specifičnih svojstava krem sira sa sniženim udjelom natrija. Snižavanje udjela natrija nije utjecalo na udio proteina, mliječne masti i vode, aktivitet vode, kiselost i boju krem sira (P>0,05). Međutim, redukcija natrija je značajno utjecala na mineralni sastav, mazivost i senzorska svojstva. Primjena mješavina soli na bazi kalija značajno povećava vrijednost omjera K:Na. Sirevi koji su sadržavali mješavinu soli Salut® od potrošača su dobili ocjene najbliže kontrolnom siru, u usporedbi s ostalim zamjenama. Ovo istraživanje pokazuje da je moguće smanjenje udjela natrija u krem siru za 35 % primjenom nutritivno vrijednih mješavina soli na bazi kalija, bez narušavanja prihvatljivosti proizvoda.
Bibliografija: 65 jed.
Summary ; Sažetak.
Keywords: Sir -- Krem sir -- Fizikalno-kemijska svojstva -- Natrij -- Kalijev klorid -- Mazivost -- Senzorska analiza